PROBLEMS OF PRODUCTION ACCOUNTING AND PROCESSING AGRICULTURAL PRODUCTS IN THE CONDITIONS OF MARKET RELATIONS - Abdullaev Abdurauf (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Strengthening the economic independence of the Republic of Uzbekistan, the formation of market relations require an increase in the efficiency of using the existing production capabilities of the national economy in general, agriculture in particular and its leading branch - crop production in particular. Therefore, the current situation in the agriculture of the republic requires the development of scientifically sound methods for choosing directions for the development of production intensification processes, taking into account regional, zonal, soil, natural and climatic features and new economic relations.